2012
DOI: 10.1103/physrevc.85.035805
|View full text |Cite
|
Sign up to set email alerts
|

Quark core impact on hybrid star cooling

Abstract: In this paper we investigate the thermal evolution of hybrid stars, objects composed of a quark matter core, enveloped by ordinary hadronic matter. Our purpose is to investigate how important are the microscopic properties of the quark core to the thermal evolution of the star. In order to do that we use a simple MIT bag model for the quark core, and a relativistic mean field model for the hadronic envelope. By choosing different values for the microscopic parameters (bag constant, strange quark mass, strong c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…We refer the reader to [135] for details, but the figure illustrates that, given our poor knowledge of the size and density extent of the various pairing gaps, nearly indistinguishable cooling curves can be obtained with very different dense matter models, i.e with or without hyperons and/or with or without quark matter. Complementary studies, as, e.g., in [136,137,138,139], confirm this conclusion.…”
Section: Can Quark Matter Be Detected From Cooling Observations?mentioning
confidence: 60%
“…We refer the reader to [135] for details, but the figure illustrates that, given our poor knowledge of the size and density extent of the various pairing gaps, nearly indistinguishable cooling curves can be obtained with very different dense matter models, i.e with or without hyperons and/or with or without quark matter. Complementary studies, as, e.g., in [136,137,138,139], confirm this conclusion.…”
Section: Can Quark Matter Be Detected From Cooling Observations?mentioning
confidence: 60%
“…More precisely, recent observations have set new high mass constraints for neutron * vdexheim@kent.edu † JSFroschauer@lbl.gov ‡ negreiros@fias.uni-frankfurt.de § schramm@fias.uni-frankfurt.de stars (PSR J1614-2230 [1] being the most important), and equations of state aimed to describe compact stars are thus expected to provide objects with high masses [2][3][4][5][6]. In the case of hybrid stars (neutron stars with a quark core in its center), a quark phase based on a simple non-interacting quark model like the MIT bag model tends to reduce the maximum mass significantly (see the discussion in [7]). A quark phase that includes strong repulsive interactions, however, may have an equation of state quite similar to a purely hadronic one.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that at low temperatures and high densities there might be a first-order phase transition between hadronic and quark matter inside neutron stars [35][36][37][38][39][40][41]. Although the density at which such a phase transition occurs is unknown it is expected to be several times the nuclear saturation density.…”
Section: Phase Transitionsmentioning
confidence: 99%